THE WAQF MODELS FOR HIGHER EDUCATION: Malaysia's Experience and Challenges in Strengthening a Waqf-Based Higher Education System - Muhammad Don, Mohd. Ali bin; Rosli, Mohd. Rilizam bin; Mohd. Senin, Mohd. Shukri bin; Husain, Mohd. Huefiros Efizi bin; Ahmad, Mohd. Farhan bin; Hj. Mohiddin, Hjh. Mas Nooraini binti; Yusof, Kamaru Salam; Kurniawan, Cecep Soleh (Al-Risalah, 2025)
This article analyses the waqf model for education in Malaysia by assessing the implementation of educational waqf, its achievements, and the challenges it faces. This study also examines how waqf can serve as a mechanism to strengthen Malaysia's education system. This study examines various initiatives and programmes undertaken by waqf agencies and educational institutions in Malaysia to improve access to higher education and to provide students in need with facilities and funding. This qualitative study employs a document analysis approach, drawing on research data from priorrom prior studies and authentic, up-to-date written documents. The study's findings present several models of waqf implementation in higher education in Malaysia. These models can be applied by other higher education institutions, with minor adjustments appropriate to the local educational context. This is significant in light of the waqf's role in education, which has been vigorously pursued for thousands of years.